2017
DOI: 10.1371/journal.pone.0183901
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA miR-301a is a novel cardiac regulator of Cofilin-2

Abstract: Calsarcin-1 deficient mice develop dilated cardiomyopathy (DCM) phenotype in pure C57BL/6 genetic background (Cs1-ko) despite severe contractile dysfunction and robust activation of fetal gene program. Here we performed a microRNA microarray to identify the molecular causes of this cardiac phenotype that revealed the dysregulation of several microRNAs including miR-301a, which was highly downregulated in Cs1-ko mice compared to the wild-type littermates. Cofilin-2 (Cfl2) was identified as one of the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 63 publications
(61 reference statements)
1
9
0
Order By: Relevance
“…Expression of genes encoding sarcomere proteins, such as myosin heavy chain 6 ( myh6) , myosin heavy chain 7 ( myh7 ), ventricle myosin heavy chain like ( vmhcl ), troponin T ( tnnt2a ), myopalladin ( mypn ) and four and a half LIM domains 2a ( fhl2a ), was significantly downregulated in VCAP1X2 mutants compared to WT. Expression levels of two natriuretic peptides ( nppa , nppb ) were substantially increased in VCAP1X2 mutant heart, similar to other DCM animal models 25 . We then compared expression levels of the sarcomere modulator, smyd1b 6 , stress response regulators [integrin subunit beta1 binding protein 2 ( itgb1bp2 ) 26 and ankyrin repeat domain 1 ( ankrd1 ) 27 ] and chaperones ( hsp90aa1.1 , unc45b , αB-crystallin/ cryabb ) 28 , 29 in VCAP1X2 mutant and WT hearts (Fig.…”
Section: Resultssupporting
confidence: 74%
“…Expression of genes encoding sarcomere proteins, such as myosin heavy chain 6 ( myh6) , myosin heavy chain 7 ( myh7 ), ventricle myosin heavy chain like ( vmhcl ), troponin T ( tnnt2a ), myopalladin ( mypn ) and four and a half LIM domains 2a ( fhl2a ), was significantly downregulated in VCAP1X2 mutants compared to WT. Expression levels of two natriuretic peptides ( nppa , nppb ) were substantially increased in VCAP1X2 mutant heart, similar to other DCM animal models 25 . We then compared expression levels of the sarcomere modulator, smyd1b 6 , stress response regulators [integrin subunit beta1 binding protein 2 ( itgb1bp2 ) 26 and ankyrin repeat domain 1 ( ankrd1 ) 27 ] and chaperones ( hsp90aa1.1 , unc45b , αB-crystallin/ cryabb ) 28 , 29 in VCAP1X2 mutant and WT hearts (Fig.…”
Section: Resultssupporting
confidence: 74%
“…However, when cofilin-2 expression is knocked down in cultured cardiomyocytes, a marked elongation of thin filaments is observed and proper I-band striations are lost (Kremneva et al 2014 ). In a mouse model for DCM, the calsarcin knockout mouse, cofilin-2 expression was increased due to a decrease in miRNA miR-301a expression and was subsequently shown to be a direct target for this miRNA (Rangrez et al 2017 ). Cofilin-2 function is regulated by phosphorylation, and fasudil, an inhibitor of ROCK (Rho kinase), which has a protective effect against cardiac dysfunction, prevents its phosphorylation and promotes the organisation of actin filaments (Lai et al 2017 ).…”
Section: Proteins Involved In Actin Filament Turnover and Their Role mentioning
confidence: 99%
“…The enrichment of miR-301a in active cardiomyocytes was originally determined from our miRNA screening study in the hearts of neonatal rodents[26], which was recently confirmed by Rangrez et al[24], who detected much higher expression of miR-301a in isolated cardiomyocytes than in fibroblasts. That study also found that miR-301a negatively regulates SRF signaling through inhibiting the expression of the target gene Cofilin-2 in cardiomyocytes, suggesting the therapeutic potential of miR-301a in the treatment of cardiac disorders caused by the deregulation of Cofilin-2[24]. Here, we first showed that miR-301a has a high level in the hearts of late-stage embryos, while it is low in undifferentiated ES cells and cardiomyocytes in early-stage embryos.…”
Section: Discussionmentioning
confidence: 62%
“…In the current study, we identified miR-301a as a highly enriched miRNA in embryonic and neonatal cardiomyocytes. Although overexpression of miR-301a is frequently observed in diverse tumor types, promoting cell proliferation, invasion, and metastasis of cancer cells[21-23], the functional properties of miR-301a in the heart remain unclear, except one recent report indicating that miR-301a is a novel cardiac regulator of Cofilin-2 in cardiomyocytes[24]. In contrast to its function in tumors, miR-301a may have tissue-specific functions in the heart.…”
Section: Introductionmentioning
confidence: 99%